Inducing Fe 3d Electron Delocalization and Spin-State Transition of FeN4 Species Boosts Oxygen Reduction Reaction for Wearable Zinc–Air Battery - Chen, Shengmei; Liang, Xiongyi; Hu, Sixia; Li, Xinliang; Zhang, Guobin; Wang, Shuyun; Ma, Longtao; Wu, Chi‑Man Lawrence; Zhi, Chunyi; Zapien, Juan Antonio (Nano-Micro Letters, 2023)
Transition metal–nitrogen–carbon materials (M–N–Cs), particularly Fe–N–Cs, have been found to be electroactive for accelerating oxygen reduction reaction (ORR) kinetics. Although substantial efforts have been devoted to design Fe–N–Cs with increased active species content, surface area, and electronic conductivity, their performance is still far from satisfactory. Hitherto, there is limited research about regulation on the electronic spin states of Fe centers for Fe–N–Cs electrocatalysts to improve their catalytic performance. Here, we introduce Ti3C2 MXene with sulfur terminals to regulate the electronic configuration of FeN4 species and dramatically enhance catalytic activity toward ORR. The MXene with sulfur terminals induce the spin-state transition of FeN4 species and Fe 3d electron delocalization with d band center upshift, enabling the Fe(II) ions to bind oxygen in the end-on adsorption mode favorable to initiate the reduction of oxygen and boosting oxygen-containing groups adsorption on FeN4 species and ORR kinetics. The resulting FeN4–Ti3C2Sx exhibits comparable catalytic performance to those of commercial Pt-C. The developed wearable ZABs using FeN4–Ti3C2Sx also exhibit fast kinetics and excellent stability. This study confirms that regulation of the electronic structure of active species via coupling with their support can be a major contributor to enhance their catalytic activity. Highlights: 1 The strong interaction between Ti3C2Sx and FeN4 species induces the central metal Fe(II) in FeN4 species with intermediate spin state transferred to high spin state, in which the latter is favorable to initiate the reduction of oxygen. 2 This strong interaction induces a remarkable Fe 3d electron delocalization with d band center upshift, boosting oxygen-containing groups adsorption on FeN4 species and oxygen reduction reaction kinetics. 3 The resulting FeN4–Ti3C2Sx with FeN4 moieties in high spin state exhibits high half-wave potential of 0.89 V vs. RHE and high limiting current density of 6.5 mA cm−2, enabling wearable zinc–air battery showing a good discharge performance with a maximum power density of 133.6 mW cm−2.